Poverty Impact of Rising Maize Prices in Kenya - Jörgen Levin (Örebro University School of Business, 2010)
The recent hike in food prices has been of great concern to policymakers, international organisations and donor agencies. In this paper we discuss, both from a partial and general equilibrium perspective, the impact of the recent price increase on maize on Kenyan households. Simulating a 100% increase in maize prices, we find that the headcount ratio in urban areas increased by 3-4 percentage unit points, depending on the size of windfall gain to producers. Based on the assumption that the price shock is passed through in total to the farmers, food poverty in the rural areas could be reduced by almost 14%. If incomes are not passed through, rural food poverty would increase quite significantly in some provinces. It is the poorest of the poor in both urban and rural areas who are most adversely affected. Policy reforms, which would reduce marketing margins and fertiliser prices, would be important factors in promoting a positive impact on performance in the maize sector. The regional maize trade within East Africa seems to have a role to play, and exploring the impact of total integration of the maize markets could be a topic of further research.
Keywords: O12; O18; Q11; Q18; 330; Food crisis; maize; Kenya; poverty; distribution; net benefit ratio; CGE